An update on the pharmacotherapy of neovascular age-related macular degeneration. (June 2013) - Freund, K Bailey; Mrejen, Sarah; Gallego-Pinazo, Roberto
<x xml:space="preserve">Abstract</x> Introduction: Neovascular age-related macular degeneration (AMD) is currently the most common cause of legal blindness in industrialized countries. The advent of pharmacotherapy with intravitreal VEGF inhibitors has greatly improved outcomes for the treatment of this disease. Areas covered: The present review is divided into two major sections: the period prior to the use of anti-VEGF agents (triamcinolone acetonide, verteporfin photodynamic therapy) and the period following their introduction (pegaptanib sodium, bevacizumab, ranibizumab, aflibercept). The main pharmacological and clinical characteristics of each therapy are summarized. Expert opinion: Monotherapy with anti-VEGF agents is currently the 'gold standard' for treating neovascular AMD, but, with several drug choices and various different dosing regimens available, there is still wide variability in how individual clinicians manage their patients. Despite improved visual outcomes, there remains a significant unmet need for better treatments as the frequent office visits and injections associated with anti-VEGF therapy are costly and place a significant burden on patients, their family members and physicians.